Pharmacological Correctors of Mutant CFTR Mistrafficking - Pedemonte, Nicoletta; Galietta, Luis (Frontiers in Pharmacology, 2012)
The lack of phenylalanine 508 (ΔF508 mutation) in the cystic fibrosis (CF) transmembrane conductance regulator (CFTR) Cl− channel represents the most frequent cause of CF, a genetic disease affecting multiple organs such as lung, pancreas, and liver. ΔF508 causes instability and misfolding of CFTR protein leading to early degradation in the endoplasmic reticulum and accelerated removal from the plasma membrane. Pharmacological correctors of mutant CFTR protein have been identified by high-throughput screening of large chemical libraries, by in silico docking of virtual compounds on CFTR structure models, or by using compounds that affect the whole proteome (e.g., histone deacetylase inhibitors) or a single CFTR-interacting protein. The presence of multiple defects of the CFTR protein caused by the ΔF508 mutation and the redundancy of quality control mechanisms detecting ΔF508-CFTR as a defective protein impose a ceiling to the maximal effect that a single compound (corrector) may obtain. Therefore, treatment of patients with the most frequent CF mutation may require the optimized combination of two drugs having additive or synergic effects.